Bryophyte cover estimation in a boreal black spruce forest using airborne lidar and multispectral sensors - Gower, Stith T.; Ahl, Douglas E.; Peckham, Scott D. (Elsevier, 2009)
Bryophytes are the dominant ground cover vegetation layer in many boreal forests and in some of these forests the net primary production of bryophytes exceeds the overstory. Therefore it is necessary to quantify their spatial coverage and species composition in boreal forests to improve boreal forest carbon budget estimates. We present results from a small exploratory test using airborne lidar and multispectral remote sensing data to estimate the percentage of ground cover for mosses in a boreal black spruce forest in Manitoba, Canada. Multiple linear regression was used to fit models that combined spectral reflectance data from CASI and indices computed from the SLICER canopy height profile. Three models explained 63 ? 79% of the measured variation of feathermoss cover while three models explained 69 ? 92 % of the measured variation of sphagnum cover. Root mean square errors ranged from 3-15% when predicting feathermoss, sphagnum, and total moss ground cover. The results from this case study warrants further testing for a wider range of boreal forest types and geographic regions.
Keywords: Moss; Sphagnum; Carbon cycling; Boreal forest; CASI; SLICER; Bryophyte cover